130k views
10 votes
Given

f
(
x
)
=

x

2
f(x)=−x−2, find
f
(

6
)
f(−6).

User Fernanda
by
6.4k points

1 Answer

8 votes

Answer:


\boxed{\tt \: f( - 6) = 4}

Explanation:

Given polynomial :-


\sf \: f(x) = - x - 2

To Find :-


\sf \: f( - 6)

Solution :-


\sf \implies \: f(x) = - x - 2


\underline{ \rm \: Substitute \: the \: value \: of \: x \: that \: is \: 6 \: i nstead \: of \: x \: on \: the \: LHS \: and \: RHS \: of \: the \: given \: equation :-}

That is ,


\sf \implies \: f( - 6) = - ( - 6) - 2


\underline{ \rm \: Simplify \: the \: RHS \: on \: t he \: given \: equation :-}

As we know that "-" and "-" equals to "+". So "-(-6)" would be represented as +6 (6).


\sf \implies \: f( - 6) = + 6 - 2

Subtract 6 and 2 :-


\sf \implies \: f( - 6) = 6 - 2


\sf \implies \: f( - 6) = 4

This can't be simplified more . Hence ,


\rm \: The \: value \: of \: f(-6) \: would \: be \: \boxed{ \bf 4} \rm .


\rule{175pt}{2pt}

I hope this helps!

User JustGettinStarted
by
5.6k points